ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI INTERNET BASED CORPORATE GOVERNANCE DISCLOSURE PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hardianto, Jalasena Putra; Ulum, Ihyaul; Anwar, A. Syaiful Hidayat (Universitas Muhammadiyah Malang)
This study aims to knowing the determinants of internet based corporate governance disclosureby Indonesian Banking Companies Listed. Internet based corporate governance disclosure usedan dependent variable and measured using 22 aspect that disclosure on official website. Size ofCompanies, Age of Companies Listed, and Dispertion Ownership used an independent variable.Size of Company measured using Log of Total Asset. Age Of companies Listed measured usingdifference of date companies listed minus date of research. Dispertion ownership measuredusing ownership of stock eâ€5%. Analysis techniques data using WarpPLS 3.0. This study foundSize of Companies positively and significantly effect to IBCGD. Age of Companies Listed andDispertion Ownership havenâ€™t effect to IBCGD.Ke ywords: Internet Based Corporate Governance Disclosure (IBCGD), Size of Companies,Age of Companies Listed, Dispertion Ownership